Interpersonal Neural Synchronization During Cooperative Behavior of Basketball Players: A fNIRS-Based Hyperscanning Study - Li, Lin; Wang, Huiling; Luo, Huiyu; Zhang, Xiaoyou; Zhang, Ruqian; Li, Xianchun (Frontiers in Human Neuroscience, 2020)
Accumulating evidence has consistently shown that team-based sports (such as basketball) are beneficial to interpersonal cooperation. However, its neural correlate remains to be discovered, especially in the perspective of two-person neuroscience. In this study, 12 dyads of basketball players and 12 dyads of college students who had no experience of team-based sports training were asked to perform joint-drawing task and control task. During task performance, neural activities were recorded in frontal area by the functional near-infrared spectroscopy (fNIRS)-based hyperscanning approach. The results demonstrated that dyads of basketball players were faster to finish joint-drawing task and showed higher subjective cooperativeness than dyads of college students. Meanwhile, significant interpersonal neural synchronization (INS) was observed in the dorsolateral prefrontal area only when pairs of basketball players performed joint-drawing task, but not control task. Therefore, we provide the first piece of inter-brain evidence for enhanced cooperative behavior in the individuals with team-based sports training, which could make us deeply understand exact neural correlate for experience-dependent changes of cognitions in humans.